Special Legal Regimes and Their Status under the Lithuanian Legal System - Vaičaitis, Vaidotas A. (Teisė, 2020)
Based on the constitutional approach, this article examines three special legal regimes in the Lithuanian legal system: the state of emergency, disaster management regime, and quarantine. The article uses four methodological criteria to reveal the differences and similarities between these legal regimes: a) the basis for the declaration of a particular legal regime, b) the subjects of their declaration and management, c) their duration, and d) the special measures applied during them, including human rights restrictions.